2022
DOI: 10.3390/jcm11030662
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis Measure by Carotid Ultrasound and Inflammatory Activity in Patients with Rheumatoid Arthritis and Spondylarthritis

Abstract: Objective: To compare the effect of inflammation on subclinical atherosclerosis using carotid ultrasound in patients with rheumatoid arthritis (RA) and spondyloarthritis (SpA). Methods: Cross-sectional study including 347 participants (148 RA, 159 SpA, and 40 controls). We measured the carotid intima media thickness (cIMT) and detection of atheromatous plaques using carotid ultrasound. We recorded disease activity (DAS28-CRP/ASDAS-CRP) and traditional cardiovascular risk factors. We performed descriptive, biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…These results support the need for the early assessment of CVD risk in all subjects with pre-clinical RA and RA [7]. A Spanish group [8], in a cross-sectional study including 347 participants (148 RA, 159 SpA, and 40 controls), which measured the carotid intima media thickness (cIMT) and looked for atheromatous plaques using carotid ultrasound, underlined the greater role of disease activity in subclinical atherosclerosis in patients with RA than in those with SpA. Specifically, the authors showed that cIMT correlated with the mean C-reactive protein (CRP) during the previous 5 years in RA but not with CRP levels at the chosen sampling time-point.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…These results support the need for the early assessment of CVD risk in all subjects with pre-clinical RA and RA [7]. A Spanish group [8], in a cross-sectional study including 347 participants (148 RA, 159 SpA, and 40 controls), which measured the carotid intima media thickness (cIMT) and looked for atheromatous plaques using carotid ultrasound, underlined the greater role of disease activity in subclinical atherosclerosis in patients with RA than in those with SpA. Specifically, the authors showed that cIMT correlated with the mean C-reactive protein (CRP) during the previous 5 years in RA but not with CRP levels at the chosen sampling time-point.…”
supporting
confidence: 75%
“…However, they did not find such differences in patients with spondyloarthritis (SpA). Furthermore, in patients with moderate-high disease activity, cIMT was greater in patients with RA than in those with SpA after adjusting for age, sex, disease course, and cardiovascular risk factors [8]. Finally, subclinical atherosclerosis measured by carotid ultrasound in patients with RA and SpA was comparable when the disease was well controlled.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The weaker inflammatory response that characterizes axSpA compared with other IRD, the Clean revised SAR-D-22-00160 difficulty of objectively measuring the disease activity, and the limited sample size of the existing studies are factors that could explain the contradictory results of previous studies, most of which failed to demonstrate this association [14][15][16][17]. In this regard, a recent study by Rojas-Gimenez et al found no association between cIMT and ASDAS-CRP, nor with the mean CRP values of the previous five years, unlike what occurred in RA [34]. It is widely accepted that systemic inflammation in IRD can significantly influence classic risk factors like dyslipidemia, insulin resistance, or obesity [35].…”
Section: Discussionmentioning
confidence: 98%
“…Whether disease activity can increase atherosclerosis to a similar extent in individuals with spondyloarthritis as in individuals with RA is currently uncertain. This question was addressed by Rojas-Gimenez and colleagues [ 21 ] in the present Special Issue. Ultrasound-determined carotid intima–media thickness (cIMT) and plaque were recorded in 148 patients with RA and 159 with spondyloarthritis, as well as in 40 control subjects.…”
mentioning
confidence: 79%